SPATIAL AUTOCORRELATION ANALYSIS ON CORONAVIRUS TRANSMISSION AND POPULATION DENSITY IN EAST JAVA PROVINCE 2020 - Hutabarat, Alda Natasya; Puspitasari, Nunik (Jurnal Biometrika dan Kependudukan, 2023)
Coronavirus (COVID-19) is a type of disease that has wildly spread during 2020. The transmission of this disease is connected by human activity and hygiene which also means that this disease might related with population density. The goal of this study is to discover the correlation between COVID-19 transmission with population density. The research areas used in this study is East Java Province during 2020. The data used for this study are COVID-19 confirmed cases and population density in 2020 East Java Province from Central Bureau of Statistics. Spatial Autocorrelation and Moran'I Methods used in this study discovered that there are some weak correlations (I=0,247) between COVID-19 cases and population density in East Java Province 2020. There are 9 areas with p value â‰¤0.05. These areas are Trenggalek Regency, Ngawi Regency, Madiun City with p=0.05 significant. Ponorogo Regency, Madiun Regency, Magetan Regency, Gresik Regency, Sidoarjo Regency and Surabaya City with p=0,001 significant. This discovery has some similarities with other studies.